2017
DOI: 10.1038/cgt.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Combination of p53-DC vaccine and rAd-p53 gene therapy induced CTLs cytotoxic against p53-deleted human prostate cancer cells in vitro

Abstract: Recently, the US FDA approved sipuleucel-T, which is composed of autologous DCs stimulated with a recombinant fusion protein of prostatic acid phosphatase (PAP) and granulocyte-macrophage colony-stimulating factor (GM-CSF), as the first immunotherapeutic agent for metastatic castration resistant prostate cancer (mCRPC). However, sipuleucel-T demonstrated only modest efficacy in mCPRC patients. Researchers are now investigating the potential of p53 protein as a tumor-associated antigen (TAA) loaded in DC-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Norcantharidin could induce apoptosis and inhibit proliferation of Tregs and its mechanism is probably associated with Vaccine therapy is an important and effective approach in treating many malignancies. 19,20 Several published studies have shown that GM-CSF-modified cell vaccines could induce effective antitumor immunity. 19,21 Granulocyte macrophage colony-stimulating factor plays a major role in maturation of DCs and activation of CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Norcantharidin could induce apoptosis and inhibit proliferation of Tregs and its mechanism is probably associated with Vaccine therapy is an important and effective approach in treating many malignancies. 19,20 Several published studies have shown that GM-CSF-modified cell vaccines could induce effective antitumor immunity. 19,21 Granulocyte macrophage colony-stimulating factor plays a major role in maturation of DCs and activation of CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…102 The experimental data for Ad-p53-dependent activation of lymphokine activated killer cells (LAK) and cytotoxic T lymphocytes (CTL) provide some insight into the mechanism by which Gendicine may enhance immunotherapy. 103,104 Combination with TCM. Gendicine has been combined with TCM for the treatment of cancer.…”
Section: Use Of Gendicine To Treat Head and Neck Cancermentioning
confidence: 99%
“…This suggests that combination therapy with p53-DC vaccination and Ad-p53 gene therapy together may represent a new paradigm for the treatment of metastatic castration resistant prostate cancer. 103 The chemotherapy-augmenting effects of Gendicine may act by reversing multidrug resistance (MDR) through regulation of autophagy. p53 is thought to contribute to lung cancer cell radiosensitivity by regulating autophagy and apoptosis.…”
Section: Enhancing Other Therapiesmentioning
confidence: 99%
“…In some studies, replication-deficient or replication-competent adenoviral vectors were used to deliver transgenes, which express a tumor suppressor protein or cytotoxic/suicide protein that induces cell cycle arrest or a death cascade [176,177]. More than 50% of cancers have a mutation in tumor suppressor gene p53.…”
Section: Cancer Immunotherapymentioning
confidence: 99%